The catalytic role of water in the binding site of l, d-transpeptidase 2 within acylation mechanism: A QM/MM (ONIOM) modelling. (December 2018) - Ibeji, Collins U.; Tolufashe, Gideon F.; Ntombela, Thandokuhle; Govender, Thavendran; Maguire, Glenn E.M.; Lamichhane, Gyanu; Kruger, Hendrik G.; Honarparvar, Bahareh
Abstract: Mycobacterium tuberculosis is the causative agent of Tuberculosis. Formation of 3 → 3 crosslinks in the peptidoglycan layer of M. tuberculosis is catalyzed byl, d -transpeptidases. These enzymes can confer resistance against classical β -lactams that inhibit enzymes that generate 4 → 3 peptidoglycan crosslinks. The focus of this study is to investigate the catalytic role of water molecules in the acylation mechanism of the β -lactam ring within two models; 4- and 6-membered ring systems using two-layered our Own N-layer integrated Molecular Mechanics ONIOM (B3LYP/6-311++G(2d, 2p): AMBER) model. The obtained thermochemical parameters revealed that the 6-membered ring model best describes the inhibition mechanism of acylation which indicates the role of water in the preference of 6-membered ring reaction pathway. This finding is in accordance with experimental data for the rate-limiting step of cysteine protease with the same class of inhibitor and binding affinity for both inhibitors. As expected, the ΔG # results also reveal that the 6-membered ring reaction pathway is the most favourable. The electrostatic potential (ESP) and the natural bond orbital analysis (NBO) showed stronger interactions in 6-membered ring transition state (TS-6) mechanism involving water in the active site of the enzyme. This study could be helpful in the development of novel antibiotics againstl, d -transpeptidase.